Back Cover: Catalytic Phenol Hydroxylation with Dioxygen: Extension of the Tyrosinase Mechanism beyond the Protein Matrix (Angew. Chem. Int. Ed. 20/2013). Issue 20 (22nd April 2013) - Hoffmann, Alexander; Citek, Cooper; Binder, Stephan; Goos, Arne; Rübhausen, Michael; Troeppner, Oliver; Ivanović‐Burmazović, Ivana; Wasinger, Erik C.; Stack, T. Daniel P.; Herres‐Pawlis, Sonja
<x xml:space="preserve">Abstract</x> Translating the catalytic mechanism of an enzyme to a synthetic complex is a challenging endeavor. In their Communication on page 5398 ff., S. Herres‐Pawlis, T. D. P. Stack, and co‐workers present a complex capable of the efficient catalytic oxidation of phenols to quinones by using dioxygen. The mechanism of the synthetic system is similar to that of tyrosinase, yet the substrate scope extends beyond that of the enzyme. Thus this work fulfills a goal of bioinspired chemistry.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>